2017
DOI: 10.3390/jmse5030028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Clustering Analysis of Extreme Wave Events around the UK Coastline

Abstract: Densely populated coastal regions are vulnerable to extreme wave events, which can cause loss of life and considerable damage to coastal infrastructure and ecological assets. Here, an event-based analysis approach, across multiple sites, has been used to assess the spatial footprint and temporal clustering of extreme storm-wave events around the coast of the United Kingdom (UK). The correlated spatial and temporal characteristics of wave events are often ignored even though they amplify flood consequences. Wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The Weibull distribution has been used here for general conformity with many studies [26], although some more recent studies [7,27] use a generalized Pareto distribution (GPD) with the POT data. Caires [26] undertook a comparison of extremes calculation using a 20-year shallow water (19 m) dataset from the Netherlands using five different methods.…”
Section: Identification Of Stormsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Weibull distribution has been used here for general conformity with many studies [26], although some more recent studies [7,27] use a generalized Pareto distribution (GPD) with the POT data. Caires [26] undertook a comparison of extremes calculation using a 20-year shallow water (19 m) dataset from the Netherlands using five different methods.…”
Section: Identification Of Stormsmentioning
confidence: 99%
“…For a long time, studies of storm tides have demonstrated that impacts from coastal processes under extreme conditions vary considerably along coastlines [3][4][5][6], while, more recently, a similar argument was made for the spatial variability of wave extremes and their relevance for the management of coastal hazards [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three contributions in this Special Issue analyse extreme sea-level changes, including the dynamic wave component. Slangen et al [14] undertake a global assessment of extreme sea-level allowances (i.e., the height a coastal structure needs to be elevated to keep the same frequency and likelihood of sea-level extremes under a certain sea-level rise scenario). Simpson et al [15] and Malagon Santos et al [16] undertake regional assessments of mean and extreme sea levels around Norway and extreme waves around the UK, respectively.…”
Section: Extreme Sea Levelsmentioning
confidence: 99%
“…Slangen et al [14] calculate sea-level allowances at the global scale using the Global Extreme Sea Level Analysis (Version 2) tide gauge database. In particular, they address one of the major uncertainties in future sea-level projections: the contribution of the ice sheets in Greenland and Antarctica to sea-level rise.…”
Section: Extreme Sea Levelsmentioning
confidence: 99%